PENGEMBANGAN POTENSI DESTINASI PARIWISATA SYARIAH DALAM MENINGKATKAN EKONOMI LOKAL DI WILAYAH KEDIRI JAWA TIMUR - Khairan; Aysa, Imma (AL-MANSYUR, 2022)
As the area of origin of most domestic tourists, East Java has many tourist destinations, especially religious or spiritual tourism. Like the tombs of Gus Miek and Sentono Gedong in the city of Kediri. The purpose of this study was to determine the impact of development and sharia for the economy of the surrounding community. In addition, to find out the obstacles and solutions that will be taken as an effort to develop sharia tourism. This study uses a descriptive qualitative method. Gus Miek's tomb itself is a sharia tourism where its development is managed by the tomb itself or there is no intervention from the relevant local government. This makes development not optimal and takes a long time due to financial constraints. However, there are still many positive impacts for the surrounding community such as traders, parking lot rentals, bathrooms, and travel. The development of sharia tourism in Setono Gedong from year to year is extraordinary. Such as the pavilion and other facilities such as bathrooms, facilities for worship, food stalls, etc. In addition, there is a cultural heritage site namely the Badut Temple which is protected by law so that the development of the facility received assistance from the Kediri City government and the East Java Cultural Conservation and Conservation Agency (BPCD). The development of sharia tourism is currently not, but has developed in other forms with local wisdom values such as the preservation of the temple and tomb of Mbah Wasil as cultural and religious heritage. In an effort to develop Setono Gedong religious tourism, the management and the ranks of the Kediri municipal government are developing a Religious Village. This is what makes the close relationship between residents, tourism managers, and local government officials can be well established because all three are mutually beneficial and have mutually beneficial results.